CURRENT CONCEPT OF HUMAN HERPESVIRUS TYPE 6 INFECTION - E. V. Melehina; A. D. Muzyka; M. Ju. Kalugina; A. V. Gorelov; O. L. Chugunova (SINAPS LLC, 2016)
Human herpes virus type 6 infection is widely distributed. It is extensively studied recent years due to the imperfection of diagnostics, as well as participa- tion in the formation of chronic somatic pathology. According to the international classification 2012, the human herpes virus 6A and human herpesvirus 6B are separate taxonomic units, which vary in sequence of nucleotides, structure, epidemiology, age of infection, the characteristics of flow, sensitivity to therapy. The review contains current data on clinical manifestations, methods of diagnosis and therapy of human herpes virus 6 infectionat different ages.